2023
DOI: 10.15252/embj.2022111901
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial morphology controls fatty acid utilization by changing CPT1 sensitivity to malonyl‐CoA

Abstract: Changes in mitochondrial morphology are associated with nutrient utilization, but the precise causalities and the underlying mechanisms remain unknown. Here, using cellular models representing a wide variety of mitochondrial shapes, we show a strong linear correlation between mitochondrial fragmentation and increased fatty acid oxidation (FAO) rates. Forced mitochondrial elongation following MFN2 over-expression or DRP1 depletion diminishes FAO, while forced fragmentation upon knockdown or knockout of MFN2 aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 106 publications
(175 reference statements)
1
26
0
Order By: Relevance
“…To further elucidate the role of PPARα in lipid metabolism regulation, we examined the expression of the PPARα target gene, carnitine palmitoyl transferase 1 (CPT1) . CPT1, a rate-regulating enzyme of the CPT system, resides on the mitochondrial outer membrane and facilitates the attachment of fatty acid acyl groups to carnitine . In agreement with previous findings, the hepatic expression of CPT1 of mice in the HFD group was significantly lower compared with that in the NCD group (Figure d) .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…To further elucidate the role of PPARα in lipid metabolism regulation, we examined the expression of the PPARα target gene, carnitine palmitoyl transferase 1 (CPT1) . CPT1, a rate-regulating enzyme of the CPT system, resides on the mitochondrial outer membrane and facilitates the attachment of fatty acid acyl groups to carnitine . In agreement with previous findings, the hepatic expression of CPT1 of mice in the HFD group was significantly lower compared with that in the NCD group (Figure d) .…”
Section: Resultssupporting
confidence: 85%
“…43 CPT1, a rate-regulating enzyme of the CPT system, resides on the mitochondrial outer membrane and facilitates the attachment of fatty acid acyl groups to carnitine. 44 In agreement with previous findings, the hepatic expression of CPT1 of mice in the HFD group was significantly lower compared with that in the NCD group (Figure 4d). 45 However, the CPT1 mRNA expression of mice in the group of HFD + MCDs tended to be increased.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Erin L Seifert * & György Hajn oczky ** How mitochondrial shape and substratespecific metabolism are related has been a difficult question to address. Here, new work by Ngo et al (2023) reports that mitochondrial shape-long versus fragmented-determines the activity of b-oxidation of long-chain fatty acids, supporting a novel role for mitochondrial fission products as b-oxidation hubs.…”
Section: Fuel Oxidation Under the Control Of Mitochondrial Shape And ...mentioning
confidence: 81%
“…This raised the possibility that CPT1 could integrate information about mitochondrial shape. Building on previous studies showing a lower sensitivity of CPT1 to its endogenous inhibitor, malonyl-CoA, in a curved versus a planar lipid bilayer (Frigini et al, 2020), Ngo et al (2023) reasoned that mitochondrial elongation results in fewer regions of high curvature within the mitochondrial network. Testing the sensitivity of malonyl-CoA inhibition of CPT1, they found that genetic approaches or excess nutrients that elongate or fragment mitochondria, respectively, increased or lessened malonyl-CoA's inhibition of boxidation.…”
Section: Fuel Oxidation Under the Control Of Mitochondrial Shape And ...mentioning
confidence: 99%
“…Mitochondrial tubular versus spherical morphology may also impact mitochondrial metabolic tasks; with tubular mitochondria favoring enzymatic activities in the matrix, and spherical mitochondria improving bioenergetic efficiency. Shirihai and colleagues recently demonstrated that mitochondrial fragmentation, such as observed in PP hepatocytes, increases fatty acid oxidation 39 . We further demonstrated a correlation between hepatic mitochondrial structure and function; pharmacological modulation of major nutrient signaling pathways resulted in a remodeled mitochondrial structure and its corresponding function (Fig 7).…”
Section: Discussionmentioning
confidence: 99%